Costly revenue-raising and the case for favoring import-competing industries - Xenia Matschke (Center for Economic Studies and ifo Institute (CESifo), 2005)
A standard finding in the political economy of trade policy literature is that we should expect export-oriented industries to attract more assistance than import-competing industries. In reality, however, trade policy is heavily biased toward supporting import industries. This paper shows within a standard protection for sale framework, how the costliness of raising revenue via taxation may make export subsidies less desirable and import tariffs more desirable. The model is then estimated and its predictions are tested using U.S. tariff data. An empirical estimate of the costliness of revenue-raising is also obtained.
Keywords: F16; F13; 330; protection for sale; tariffs; trade protection; Außenhandelspolitik; Außenhandelsbeschränkung; Steuererhebung; Schätzung; USA; protection for sale